Reaktualisasi Manajemen Kesiswaan dalam Mempertahankan Local Wisdom (Studi Analisis di MTs Miftahul Ulum Karangmojo, Klego, Boyolali) - Miftah, Muhammad (LP2M IAIN kUDUS, 2017)
This paper discusses how the active role of MTs Miftahul Ulum in maintaining the local culture through structural students’ management. Students’ management is one of important aspects in educational institutions. It is because base on this, institution can map and plan the future activities in an educational institution. Basically, the students’ management discusses the planning of student, students’ organization and students’ coaching so the students’ learning process in educational institutions can be success. Management pattern used in this Madrasa always considers local culture by keeping the culture and customs that exist in the community through its superior programs.